Sistem Pendidikan Negara Abad ke-21 Brunei Darussalam dalam Melestari Ketamadunan Islam Negara Zikir: Cabaran dan Harapan - Yahya, Masuriyati; Sa'ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
The education system plays an important role in contributing to the development and preserving the civilization of a country taking into account the importance of the mental, physical and spiritual, and spiritual aspects. National Education System of the 21st Century (SPN21) is a holistic education system. By using the library and a number of previous studies, this article describes the National Education System of the 21st Century (SPN21) preserving the Islamic civilization in the National Remembrance and submit education by example and has characteristic murabbi in the process of teaching and learning in SPN21 by focusing on student (student centered learning) as an approach. With it, SPN21 will give an impact in addressing the problems of globalization that such an impact on the thinking and moral development of the individual student Islam in Brunei Darussalam.